Effect of foraging activity on the shoal structure of cod ( Gadus morhua ) - DeBlois, E. M.; Rose, G. A. (Canadian Journal of Fisheries and Aquatic Sciences, 1995)
Acoustic methods used to quantify the shoaling dynamics of Atlantic cod (Gadus morhua) during their shoreward migration across the northeast Newfoundland shelf (spring 1992) showed that shoal structure and horizontal displacement were associated with the density distribution of small pelagic scatterers, for example, shrimp (Pandalus borealis). Cod speeds (to 20 km/d) were lower after encounters with shrimp (4–7 km/d). The relationship between several characteristics of the cod shoal (density, vertical spread, height off the bottom) and shrimp density was dome shaped. Internal shoal densities declined and shoal spread and height increased until shrimp densities surpassed a critical level. Above this threshold, these trends were reversed. The vertical spread of the cod shoal matched that of shrimp up to, but not beyond, a shrimp spread of 85 m. At this observed maximum in the expansion of the shoal, fish were eight body lengths apart. At all times during our survey, cod stayed within the warmer waters (> 2 °C) found at depths greater than 250 m. Our results are the first field verification of theoretical predictions and laboratory findings that shoals expand and contract in response to foraging activity and demonstrate the potential importance of cod aggregation dynamics to interpretations of trawl data.